Exemplary centre and "terra incognita"; Excursions, diplomacy, and appropriation of colonial knowledge in Belu, Timor - Hägerdal, Hans (Wacana, Journal of the Humanities of Indonesia, 2023)
The article analyses early European knowledge about Belu, a historical region in Central Timor which, although “belonging” mostly to the Dutch colonial sphere, still had a position of cultural-ritual centrality on a Timor-wide level. Before the mid-nineteenth century, the region was, from a Dutch point of view, largely unknown in terms of political hierarchies, social structure, and economic opportunities. However, three officially commissioned authors, A.G. Brouwer, W.L. Rogge, and H.J. Grijzen, wrote extensive reports about Belu in 1849, 1865, and 1904, in which they attempted to understand local society and the opportunities they offered the colonial state. The article explores history at the interstices, looking at spaces between colonial realms and the realities which blurred European preconceptions, and the local Belunese agency which can be gleaned through a critical reading of the three authors.